The Allergy Trigger Atlas: Spatial and Biological drivers of plant sensitization in China - Lv, Xinyuan; Dai, Haoxin; Zou, Hu; Wei, Bowei; Guo, Lihao; Hong, Xiaoyi; Zhang, Jingrui; Liu, Bo (Ethnobotany Research and Applications, 2025)
Background: The rising prevalence of allergic diseases in China, driven by extensive biodiversity and widespread allergenic plants, has become a significant public health concern. This study investigates the distribution patterns, phylogenetic diversity, and seasonal dynamics of allergenic plants across China to assess regional and temporal allergy risks. Methods: Using species distribution data from the Flora of China, National Specimen and Infrastructure (NSII), and GIS-based spatial analysis. Phylogenetic analysis under the APG IV framework revealed that allergenic plants are polyphyletic, distributed across multiple evolutionary lineages. Results: The findings reveal that (1) 1,668 allergenic plant species were identified, Southwest China faces the highest allergy risk, with Southern cities generally surpassing Northern China in allergy risk due to high species richness and climatic conditions favoring pollen dispersal; (2) Spring poses the highest allergy risk, seasonal analysis shows spring (March–May) as the peak period for pollen-related allergies, driven by woody plants followed by summer and autumn; (3) The distribution of allergic plant species in Chinese cities is generally scattered or random, contributing to intricate and sporadic allergic scenarios; (4) Certain evolutionary branches have high number of allergenic plant species, but the phylogeny signal of all the 38 genera is weak. Conclusions: This study provides crucial insights into the geographical and seasonal dynamics of allergic plants in China, facilitating a more informed approach to allergy management. It finds consistency in seasonal distribution conclusions. Climate affects allergic plant distribution. Suggestions are given for urban greening and travel. Keywords: Allergenic plants; China; phylogenetic diversity; sensitization pattern; seasonal distribution 摘要 背景：在中国，由于丰富的生物多样性和广泛分布的致敏植物，过敏性疾病发病率不断上升，已成为重大公共卫生问题。本研究通过探究中国致敏植物的分布格局、系统发育多样性及季节动态，评估区域性与季节性过敏风险。 材料与方法：基于《中国植物志》、国家标本资源共享平台（NSII）的物种分布数据，结合GIS空间分析技术展开研究。根据APG IV分类系统进行的系统发育分析表明，致敏植物具有多系起源特征，广泛分布于多个进化支系中。 结果：研究发现（1）共鉴定出1,668种致敏植物，中国西南地区因物种丰富度高且气候条件利于花粉传播，过敏风险居全国之首，南方城市总体风险高于北方；（2）春季（3-5月）木本植物花粉释放导致过敏风险达到峰值，夏秋季次之；（3）中国城市中致敏植物多呈分散或随机分布，形成复杂零星的致敏格局；（4）特定进化支系含致敏植物种类较多，但38个属的系统发育信号均较弱。 结论：本研究揭示了致敏植物在中国的地理与季节分布规律，为过敏防控提供了科学依据。研究验证了季节分布结论的一致性，证实气候对致敏植物分布的影响，并为城市绿化建设和民众出行提出了建议。 关键词：致敏植物；中国；系统发育多样性；致敏模式；季节分布